Knowledge hierarchy and mechanisms of power in environmental impact assessment: Insights from the Muskrat Falls hydroelectric project. (14th March 2022) - Barnard‐Chumik, Hannah; Cappe, Natalie; Giang, Amanda
Abstract: Discussions surrounding the improvement of decision‐making processes like environmental impact assessment (EIA) often emphasize pluralism in the knowledge generation process, in an effort to increase effectiveness. However, empirical research indicates that such attempts to integrate multiple ways of knowing often fall short and significant knowledge conflicts remain. Scholars suggest this may be due to inadequate attention to power in the regulatory arena. The purpose of this study is to examine how power and knowledge influence the process and outcome of EIA in a participatory context. We develop a case study analysis of the Muskrat Falls hydroelectric project, located in Labrador, Canada. We use situational analysis to analyze documents produced over the course of the EIA and semi‐structured interviews. We find evidence of pluralism in knowledge production in the EIA process, but a distinct knowledge hierarchy in EIA outcome. We argue that this knowledge hierarchy is achieved through depoliticization of the EIA process. In particular, we identify the concept of "project inertia" as a distinct mechanism of depoliticization present in EIA and make policy prescriptions to improve the Canadian EIA process. This research contributes to broader theoretical discussions about pluralism in decision‐making processes. Key Messages: There is evidence of knowledge horizontality in EIA process and hierarchy in EIA outcome. Project inertia is a mechanism of depoliticization particular to EIA, and influences its process and outcome. Lessons learned from Muskrat Falls suggest that project inertia and power inequalities can be addressed through the formation of knowledge coalitions, among other policy prescriptions. Hiérarchie des connaissances et mécanismes du pouvoir dans l'évaluation des impacts environnementaux : Quelques leçons du projet hydroélectrique de Muskrat Falls: Les discussions entourant l'amélioration des processus décisionnels tels que l'évaluation des impacts environnementaux (EIE) mettent souvent l'accent sur le pluralisme dans le processus de production de connaissances, dans un effort pour accroître l'efficacité. Toutefois, les recherches empiriques indiquent que de telles tentatives pour intégrer des connaissances diverses sont souvent insatisfaisantes et que des conflits importants demeurent. Des universitaires suggèrent que ceci puisse être dû au manque d'attention porté à la question du pouvoir dans le domaine réglementaire. Le but de la présente étude est donc d'examiner la façon dont le pouvoir et les connaissances influencent le processus et les résultats de l'EIE dans un contexte participatif. Pour ce faire, nous effectuons une étude de cas du projet hydroélectrique de Muskrat Falls, situé au Labrador, au Canada. Nous utilisons l'analyse situationnelle pour scruter les documents produits dans le cadre de l'EIE ainsi que des entrevues semi‐structurées. Nous avons remarqué des preuves du pluralisme dans la production de connaissances reliée à l'EIE mais il subsiste une hiérarchie distincte des connaissances dans les résultats de l'EIE. Nous faisons valoir que cette hiérarchie des connaissances prend place par le biais de la dépolitisation du processus d'EIE. Plus particulièrement, nous identifions le concept « d'inertie du projet » comme mécanisme distinct de dépolitisation présent dans l'EIE et nous faisons des recommandations visant à améliorer le processus canadien d'EIE. Par ailleurs, cette recherche contribue aux discussions théoriques plus larges au sujet du pluralisme dans les processus décisionnels.